PENGADAAN SARANA DAN PRASARANA DI SEKOLAH MENENGAH ATAS (SMA) NEGERI 4 KOTA PARIAMAN - Nanda, Lola Amelia; Zulmuqim, Zulmuqim; Annova, Fauzana (UIN Imam Bonjol Padang, 2023)
This research is motivated is related to the procurement of facilities and infrastructure at State Senior High School (SMA) 4 Kota Pariaman, regarding purchasing, self-manufacture, recipients of grants/aid, and repairs. This research uses a descriptive qualitative approach, data collection in this research uses interview, observation and documentation methods. The informants in this research were the Principal, Deputy Principal for infrastructure and teachers at State High School 4 Kota Pariaman. The results of the research show that the procedures for procuring facilities and infrastructure at SMA 4 Pariaman city include understanding dan awareness of the school in carrying out procurement at the school. The activities can include purchasing any missing facilities and infrastructure, making your own such as making teaching aids, learning media, school decorations, there are also activities to receive grants or assistance provided by the local government or community, as well as making improvements to existing facilities and infrastructure.